2017
DOI: 10.2147/jpr.s138519
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related beneficial and harmful effects of gabapentin in postoperative pain management – post hoc analyses from a systematic review with meta-analyses and trial sequential analyses

Abstract: BackgroundDuring the last 15 years, gabapentin has become an established component of postoperative pain treatment. Gabapentin has been employed in a wide range of doses, but little is known about the optimal dose, providing the best balance between benefit and harm. This systematic review with meta-analyses aimed to explore the beneficial and harmful effects of various doses of gabapentin administered to surgical patients.Materials and methodsData in this paper were derived from an original review, and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 114 publications
2
11
0
Order By: Relevance
“…The analysis was well executed, the number of patients robust, the quality of evidence properly evaluated, the results clearly presented, and the conclusions well supported and unambiguous. This article is entirely consistent with previous reports [2][3][4][5][6] but also brings forth additional information. The new analysis evaluated a broad surgical population, a long duration of outcomes, included additional trials, and, importantly, assessed minimally important clinical differences rather than just statistical differences.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The analysis was well executed, the number of patients robust, the quality of evidence properly evaluated, the results clearly presented, and the conclusions well supported and unambiguous. This article is entirely consistent with previous reports [2][3][4][5][6] but also brings forth additional information. The new analysis evaluated a broad surgical population, a long duration of outcomes, included additional trials, and, importantly, assessed minimally important clinical differences rather than just statistical differences.…”
supporting
confidence: 91%
“…6 Recent years have seen a reversal of fortune for perioperative gabapentinoids, brought about by improved clinical research and its synthesis into informative and actionable evidence. [1][2][3][4][5] Compared with placebo, patients receiving perioperative gabapentinoids sometimes have pain and/ or opioid consumption that is less, statistically, but small in magnitude (a few percentage points less pain and sparing only a few milligrams of opioid) and short-lived (often only a day) but not clinically meaningful and not preventing chronic postsurgical pain or opioid use.…”
mentioning
confidence: 99%
“…Recently, the study performed by Fabritius et al 92 demonstrated that they could not confirm a distinct relationship between the dose of GBP and the consumption of opioids, dividing all treatments into subgroups despite single or multiple doses, preoperative or postoperative administrations. In the present study, we presented an NMA to validate the effect of analgesic and risk of adverse events by a series of doses of PGB or GBP administration.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the use in the postoperative period is associated with multiple described side effects. 3,4,5,6,7 A study on the use of gabapentin following total knees determined, "On the basis of this meta-analysis, we found no evidence to support the routine use of gabapentinoids in the management of acute pain following total knee arthroplasty." 8 And in a large meta-analysis of pain after surgery, it was determined, "No clinically significant analgesic effect for the perioperative use of gabapentinoids was observed.…”
mentioning
confidence: 82%